DETERMINAN FAKTOR FRAUD DENGAN KEEFEKTIFAN PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI (Studi Pada Organisasi Perangkat Daerah Kabupaten Keerom) - Bonsapia, Melyanus; Falah, Syaikhul; Bharanti, Bonifasia Elita (Fakultas Ekonomi, Universitas Cenderawasih, 2020)
he purpose of this study was to test and analyze the Determinant of the Fraud Factor with theEffectiveness of Internal Control as a Moderation Variable in the Keerom District GovernmentOrganizations. The research population were all 28 Regional Apparatus Organizations, where thesample in this study was the Head of the Regional Apparatus Organization, Head of Division.Accounting and Head of subdivision.General/administration in each Regional ApparatusOrganization. The Test was accomplished about 77 sample respondents by using probabilitysampling. Data collection was collecting by directing a survey. Hypothesis testing was empiricallytested by using Smart PLS.The results showed that information asymmetry was affecting the tendency of accounting fraud. Thepursuance of accounting regulations was not affecting the likelihood of accounting fraud. Thesuitability of compensation has influenced the leaning of accounting fraud. The leadership hasinfluenced the tendency of accounting fraud. The effectiveness of internal control has moderated theinformation asymmetry towards accounting fraud tendencies. The internal control has moderatedthe accounting enforcement of trends in accounting fraud. The usefulness of internal controls hasmoderated the suitability of compensation for accounting fraud tendencies. The effectiveness ofinternal controls moderates leadership towards accounting fraud trends.